An unusual coronoid fracture in a fragment of ulna recovered from the Prehistoric site of Buraca da Moira Rock Shelter (Boa Vista, Leiria) - Assis, Sandra (2019)
In 2015, several disarticulated human skeletal remains were identified in the top layers of the prehistoric site of Buraca da Moira Rock Shelter (Boa Vista, Leiria), during the archaeological excavation carried out under the scope of the EcoPLis — Human Occupations in the Pleistocene Ecotones of the River Lis project. The recovery of chert, and quartzite blanks, a schist plate, as well as adornments in bone and shell indicates a Late Neolithic-Chalcolithic chronology. The disarticulated human assemblage, composed of a total of 129 bone and tooth fragments, allowed the estimation of a minimum number of six individuals. Among the remains recovered, an upper portion of an adult right ulna lacking the coronoid process was identified. Replacing it, a semi-oval groove with smooth contours and exposing some trabecular bone was observed. The location, type of bone change, and the observed signs of bone healing are consistent with an uncommon trauma: a fracture of the coronoid process. In the differential diagnosis, both postmortem changes and developmental disturbances were considered but later excluded. The mechanisms that underlie the bone changes are discussed in light of the clinical and paleopathological literature.